Dz13: c-Jun Downregulation and Tumour Cell Death - Elahy, M.; Dass, Crispin (Blackwell Publishing, 2011)
DNAzymes (DNA enzymes and deoxyribozymes) are synthetic, single-stranded DNA-based catalysts engineered to bind to their complementary sequence in a target messenger RNA (mRNA) through Watson–Crick rules for base-pairing and cleave the mRNA at predetermined phosphodiester linkages. Dz13, a DNAzyme that cleaves c-Jun mRNA, has been found to have efficacious effects against tumours directly, activity against tumour-induced angiogenesis, inhibition of neointima formation after arterial injury and control of inflammatory responses. Recent studies in endothelial cells demonstrate that the off-target effects of Dz13 may in fact be driving some of these potentially therapeutic effects, although no mechanisms have been clearly defined in tumour cells. Recent data show that Dz13 is capable of inhibiting more types of tumours and potently induces apoptosis in a panel of tumour cell lines. Hand-in-hand with in vivo testing, Dz13 has been formulated into a biocompatible nanoparticle, enabling its full potential to be realized. Its chemistry is partly responsible for its activity against tumour cells, but it is safe to use in vivo and surprisingly shows little harmful effects against normal cells. These findings provide hope that Dz13 may be useful clinically for the treatment of a variety of cancers.